Handbook of pharmaceutical biochemistry for health professionals : a guide book for Doctors of Pharmacy, MBBS, BDS, BSc and MSc Chemistry students - Wahab, Abdul; Khan, Shahid Ullah (Germany : Lap Lambert Academic Publishing, 2015)
The first edition of Handbook of Pharmaceutical biochemistry for health professionals is designed and written to provide accurate, current information about the basic concept of Biochemistry in a fascinating and lucid manner.
CHAPTER 1 Carbohydrates -- CHAPTER 2 Lipids -- CHAPTER 3 Protein and amino acids -- CHAPTER 4 Nucleic acids -- CHAPTER 5 Vitamins -- CHAPTER 6 Enzymes -- CHAPTER 7 Metabolic fate of biomolecules (a) carbohydrate -- CHAPTER 8 Metabolic fate of biomolecules (b) lipids -- CHAPTER 9 Metabolic fate of biomolecules (c) amino acids.
Includes bibliographical references.
Keywords: BIOCHEMISTRY -- MANUALS